2019
DOI: 10.1007/s13205-019-1585-z
|View full text |Cite
|
Sign up to set email alerts
|

An insight into the anticancer mechanism of Tribulus terrestris extracts on human breast cancer cells

Abstract: Tribulus terrestris (TT), a herb belonging to Zygophyllaceae family is widely used due to its medicinal properties. This study was undertaken to elucidate the anticancer mechanism of TT on MCF-7 breast cancer cells. Cytotoxic effect of the herb was assessed by 3-(4,5-diethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assay. Apoptotic potential was assessed through DNA fragmentation, TUNEL and caspase 3 activity assays. Expressions of genes regulating the apoptotic pathway were examined by RT-PCR and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 26 publications
(25 reference statements)
2
12
0
Order By: Relevance
“…Our results support the previous studies that claimed antitumor activity of T. terrestris [ 2 , 3 ]. In this study, the extract of the whole plant was investigated, while Patel et al, Goranova et al, and Angelova et al proved both cytotoxic and antiapoptotic effect of its seed and leaf against MCF7 and MCF-10A cells [ 4 , 5 , 45 ]. Previously, Majed and Ali demonstrated cytotoxic activity of the pollen extract of T. domingensis against MCF7 cells [ 11 ], while the vegetative part of the same plant was tested in this study against the same cell line and showed twelve folds more activity compared to the pollen part.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results support the previous studies that claimed antitumor activity of T. terrestris [ 2 , 3 ]. In this study, the extract of the whole plant was investigated, while Patel et al, Goranova et al, and Angelova et al proved both cytotoxic and antiapoptotic effect of its seed and leaf against MCF7 and MCF-10A cells [ 4 , 5 , 45 ]. Previously, Majed and Ali demonstrated cytotoxic activity of the pollen extract of T. domingensis against MCF7 cells [ 11 ], while the vegetative part of the same plant was tested in this study against the same cell line and showed twelve folds more activity compared to the pollen part.…”
Section: Resultsmentioning
confidence: 99%
“…Although T. terrestris has not been extensively studied for detailed anticancer activities, several investigations indicated its potential cytotoxic activity. In a recent study, Patel et al (2019) reported that methanolic and saponin extracts of T. terrestris exhibited cytotoxic activity probably through extrinsic and intrinsic apoptotic pathways [ 4 ]. Namely, the seed and leaf extracts induced apoptosis and DNA fragmentation in human breast cancer MCF-7 cells.…”
Section: Introductionmentioning
confidence: 99%
“…In the study by Apurva et al, the extract of the Tribulus terrestris plant seems to increase the caspase 3 activity of the human breast cancer cell line [51]. In the study by Masoud et al, the herb is also found to have anticancer activity against prostate and colon cancer cell lines [52].…”
Section: Resultsmentioning
confidence: 97%
“…Naz ability at 100 ppm concentration and 80.54% cell viability at 12.50 ppm on MCF-7 cell line. It had been reported that the leaves of the plant cause 98.46 % and 69.51 % cell viability on MCF-7 cells at 100 ppm and 12.50 ppm concentrations, respectively [30]. The biological activity of a plant sample varies according to many conditions such as the solvent used in the isolation of its phenolic compounds, extraction technique, climate, coordinates, altitude, soil quality and fertilizer used [31,32].…”
Section: Mtt Assaymentioning
confidence: 99%